2009
DOI: 10.1590/s0100-879x2009000400006
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant and antimicrobial activities of bitter and sweet apricot (Prunus armeniaca L.) kernels

Abstract: The present study describes the in vitro antimicrobial and antioxidant activity of methanol and water extracts of sweet and bitter apricot (Prunus armeniaca L.) kernels. The antioxidant properties of apricot kernels were evaluated by determining radical scavenging power, lipid peroxidation inhibition activity and total phenol content measured with a DPPH test, the thiocyanate method and the Folin method, respectively. In contrast to extracts of the bitter kernels, both the water and methanol extracts of sweet … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
80
1
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 133 publications
(91 citation statements)
references
References 27 publications
7
80
1
1
Order By: Relevance
“…In another experiment the DPPH SA of the extract of thuja twigs was found to be 73.35±1.04% at 300 μg/ml (Dubey and Batra 2009). The DPPH radical scavenging activities of water and methanol extracts from other Prunus species fruit (apricot) cultivars were also reported by Yigit et al (2009). According to this research a concentration of 100 μg/mL, the water and methanol extracts of the sweet kernel exhibited 89.9 and 87.7% scavenging activity, respectively.…”
Section: Dpph Radical Scavenging Activitiessupporting
confidence: 56%
See 2 more Smart Citations
“…In another experiment the DPPH SA of the extract of thuja twigs was found to be 73.35±1.04% at 300 μg/ml (Dubey and Batra 2009). The DPPH radical scavenging activities of water and methanol extracts from other Prunus species fruit (apricot) cultivars were also reported by Yigit et al (2009). According to this research a concentration of 100 μg/mL, the water and methanol extracts of the sweet kernel exhibited 89.9 and 87.7% scavenging activity, respectively.…”
Section: Dpph Radical Scavenging Activitiessupporting
confidence: 56%
“…Chen et al (1999) reported that phenolic compounds such as quercetin were also effective in preventing lipid oxidation in both raw and cooked turkey during 7 days of storage. According to study conducted by Yigit et al (2009) in another prunus variety (apricot) the highest percent inhibition of lipid peroxidation was found 68.6%/100 μg solid in methanol extracts of the sweet kernel. This was followed by the water extract from the same cultivar, which demonstrated 66.3% inhibition.…”
Section: Whc and Cooking Loss Of Ground Meat Treated With Tce And Psementioning
confidence: 96%
See 1 more Smart Citation
“…Durmaz and Alpaslan (2007) mentioned that apricot seeds are added to bakery products (as whole seeds or ground) in retail bakeries and also consumed as appetizers. Apricot seeds, particularly rich in lipid and protein, are potentially useful in human nutrition (Femenia et al, 1995;Alpaslan et al, 2006) along with significant amounts of oil fiber (Abd el-aal et al, 1986;Hacisefero et al, 2007) high antioxidant and antimicrobial activities (Yigit et al, 2009). Sweet apricot seeds contain more oil than bitter and such oleic acid and linoleic acid correspond to approximately 92 g*100 g -1 of the total fatty acids present in apricot seed.…”
Section: Introductionmentioning
confidence: 99%
“…Investigation of microbiological spoilage and demonstration of the antibacterial activity of the major imported fruits within Dhaka Metropolis assay Fresh fruits are vital parts of human diet because of their multi-dimensional nutritional benefits along with the traits of being natural antioxidants and antimicrobials (1)(2)(3)(4)(5)(6). Conversely, fresh fruits may play role as potential vehicles for the transmission of bacterial, parasitic and viral pathogens to the consumers ultimately leading to the possibility of the onset of food borne diseases (5)(6)(7)(8)(9)(10).…”
mentioning
confidence: 99%